Mesocarnivores in Protected Areas: ecological and anthropogenic determinants of habitat use in northern Kwa-Zulu Natal, South Africa - Pretorius, Michelle (Department of Biological Sciences, 2020)
Protected areas (PAs) form the cornerstone for most carnivore conservation strategies. However, climate change, increased isolation and human pressure along PA boundaries are together reducing the effectiveness of PAs to conserve carnivores. Mesocarnivores, in particular, frequently move beyond the boundaries of PAs where they threaten human livelihoods, and as a result, are often subject to chronic persecution. In South Africa, we know little about the conservation status of mesocarnivores both within and outside of PAs, as most research focuses on large, charismatic apex predators. The goal of my study was to leverage data collected from large carnivore studies to understand variation in mesocarnivore species richness within PAs. Camera trap surveys were conducted as part of Panthera’s 2015 national leopard monitoring programme in seven PAs across northern KwaZulu-Natal (KZN), South Africa. Using a multi-species extension of the Royle-Nichols occupancy model, my study explored environmental, interspecific and anthropogenic drivers of mesocarnivore habitat use and species richness. I found a surprisingly low number of detections (N = 356) for all five mesocarnivore species and considerable variation across PAs. Small PAs with a recent history of human disturbance supported more mesocarnivore species and at higher relative abundance. Mesocarnivore species richness was found to decline with increased vegetation and leopard abundance but increased towards the edge of PAs. Variation in species richness estimates decreased significantly with vegetation productivity and domestic dog abundance. Together these results suggest that (1) the edges may provide a refuge for mesocarnivores from more dominant species, (2) mesocarnivores exhibited resilience/adaptability to human disturbance, and (3) primary productivity and domestic dog abundance could mediate mesocarnivore distributions within PAs. My study showed that camera trap data derived from a single-species survey can be used to make inferences about non-target species to great success. Current PAs in KZN may not adequately conserve mesocarnivores, and as a result, emphasis should be placed on coexistence with mesocarnivores in marginal habitat outside of PAs.